Fatty acid transport protein 2 reprograms neutrophils in cancer - Veglia, Filippo; Tyurin, Vladimir A.; Blasi, Maria; De Leo, Alessandra; Kossenkov, Andrew V.; Donthireddy, Laxminarasimha; To, Tsun Ki Jerrick; Schug, Zach; Basu, Subhasree; Wang, Fang; Ricciotti, Emanuela; DiRusso, Concetta; et al. (Nature (London), 2019)
Polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) are pathologically activated neutrophils that are crucial for the regulation of immune responses in cancer. These cells contribute to the failure of cancer therapies and are associated with poor clinical outcomes. Despite recent advances in the understanding of PMN-MDSC biology, the mechanisms responsible for the pathological activation of neutrophils are not well defined, and this limits the selective targeting of these cells. Here we report that mouse and human PMN-MDSCs exclusively upregulate fatty acid transport protein 2 (FATP2). Overexpression of FATP2 in PMN-MDSCs was controlled by granulocyte–macrophage colony-stimulating factor, through the activation of the STAT5 transcription factor. Deletion of FATP2 abrogated the suppressive activity of PMN-MDSCs. The main mechanism of FATP2-mediated suppressive activity involved the uptake of arachidonic acid and the synthesis of prostaglandin E 2 . The selective pharmacological inhibition of FATP2 abrogated the activity of PMN-MDSCs and substantially delayed tumour progression. In combination with checkpoint inhibitors, FATP2 inhibition blocked tumour progression in mice. Thus, FATP2 mediates the acquisition of immunosuppressive activity by PMN-MDSCs and represents a target to inhibit the functions of PMN-MDSCs selectively and to improve the efficiency of cancer therapy. The lipid transporter FATP2 reprograms neutrophils to polymorphonuclear myeloid-derived suppressor cells by mediating the uptake of arachidonic acid and promoting the synthesis of prostaglandin E 2 .